A comparative study on thermal decomposition behavior of biodiesel samples produced from shea butter over micro- and mesoporous ZSM-5 zeolites using different kinetic models - Alaba, P.A.; Sani, Y.M.; Daud, W.M.A.W. (Kluwer (now part of Springer), 2016)
This study compared the kinetics of biodiesel produced over mesoporous ZSM-5 zeolites (0.3mesoZBio and 0.4mesoZBio) and conventional ZSM-5 zeolites (ZBio). The pyrolysis of each biodiesel was carried out in the presence of nitrogen at different heating rates of 10, 15 and 20 °C min−1. The reaction order, activation energy (EA) and frequency factor (A) were computed using four different models. The models are Arrhenius, Coats–Redfern, Ingraham–Marrier and Differential model. According to the computed average activation energy based on first order, the activation energies of the produced biodiesel are very close. ZBio exhibits the highest EA (86.53 kJ mol−1) compared to 0.3mesoZBio and 0.4mesoZBio (84.92 and 83.26 kJ mol−1, respectively). Therefore, it is tenable to adduce ZBio as the most stable because higher activation energy engenders higher stability.